New Spectrophotometric Methods For The Determination Of Lornoxicam In Pharmaceutical Dosage Forms - E.VENUMADHAV; T.NEEHA; P.BHARGAVI; AMREEN NISHAT; A.SWETHA; G.DEVALA RAO (International Journal of Pharma and Bio Sciences, 2010)
Two simple and sensitive visible spectrophotometric methods (A & B) for the determination of Lornoxicam (LOC) in bulk and pharmaceutical dosage forms are described. Method A is based on oxidation of drug with Ferric Chloride and subsequent complexation of Fe(II) with 2, 2’ Bipyridine to form a blood red colored species ( λmax :520 nm). Method B is based on oxidation of LOC with Ferric Chloride and chelation of Fe (II) with Bathophenanthroline to produce a blue colored chromogen (λmax: 610 nm). These methods were extended to the analysis of pharmaceutical formulations and results compared with the reference method.